KEWENANGAN BADAN PENGAWAS PEMILU DALAM PENANGANAN PELANGGARAN ADMINISTRASI DITINJAU DARI PERSPEKTIF SISTEM PERADILAN INDONESIA - Alasman Mpesau (Universitas Muhammadiyah Malang, 2021)
In the General Election and Regional Head Election Law, the Election Supervisory Board (Bawaslu) has the authority supervisory to each Election stages, it is the center for law enforcement activities of the Election (Sentra Gakkumdu) to criminal acts and carrying out the judicial functions for investigating, examining, and decided on administrative disputes of General Election and Regional Head Election. With the Bawaslu’s authority then placed as a super-body institution in the ranks of the Election Management Body, due to its essential role in building a clean and credible electoral system, it also has potential for abuse of power within it. In Law no. 48 of 2009 concerning Judicial Power has defined state institutions that have the authority to administrate judicial functions. These are the Supreme Court and Judicial Bodies that under its lines of general court, Religious Courts, Military Courts, Administrative Court (PTUN) and the Constitutional Court. The research method is normative juridical, that focuses on the analysis of the laws and regulations on General Election, Regional Head Elections and the Law on Judicial Power. The analytical tool is descriptive analysis, by describing the main issues, an analysis is carried out that was supported by case-approach related to the research. The study concludes that Bawaslu in carrying out judicial functions in its position as a semi-judicial institution has not a hierarchical relationship to the Supreme Court (MA) and the Constitutional Court (MK); however, what does exist is functional relationship.